Drót 9. adás
1. Preferential Share Sales Program: compensation vouchers, stock exchange, Brewery of Sopron. 2. Public opinion poll: elections forecast by Szonda Ipsos. 3. Infrastructural development: Nyíregyháza, Gyöngyöstarján, sewage, telephone, gas, Miskolc, loans, central transfers, lobbying, local resources. 4. Real estate swap: NIKEX headquartersl, Hungária Television Foundation, Duna TV. 5. Preview of next Drót program.